The Effect of the Educational Game Tools on Early Childhoods in the Kindergarten - Yusuf Hidayat; Ida Nurhayati; Siti Salamah; Mia Rosmiati; Ade Siti Fatimah; Lestari Lestari (Journal Corner of Education, Linguistics, and Literature, 2023)
Empirically, the educational game tools have significant benefits in stimulating interest in early childhoods’ learning. It is because psychologically early childhoods tend to be in the age of playing. The present study aims to determine the effects of using the educational game tools on early childhoods’ learning in kindergarten level. In the present study, the researchers set forth a research question: What are the effect of using the educational game tools on early childhood and teacher at Kober Sartika Asih located in Mekarmulya, Pamarican, Ciamis? To gain the answer, the researchers employ a qualitative method under a descriptive study at which they conduct series of observation towards the early childhoods’ learning activities using the educational game tools during 4 meetings in June 2023. The results show that the educational game tools are the effective media to teach the early childhoods. Based on its usage, the educational game tools give the effects such as: increasing the early childhoods’ curiosity and enthusiasm when they are participating the learning process, providing a stimulus for the early childhoods to understand the learning material given, stimulating the early childhoods’ cognitive, physical-motor, language, social-emotional competencies, and increasing enthusiasm both for the teachers during teaching and the early childhoods during learning. In conclusion, there are some positive effects of using the educational game tools to teach to the early childhoods.